Design, synthesis, and gas permeation properties of polyimides containing pendent imidazolium groups - Shrimant, Bharat; Kharul, Ulhas K.; Wadgaonkar, Prakash P. (Journal of Polymer Science Part A-Polymer Chemistry, 2018)
Film-forming polymers containing ionic groups have attracted considerable attention as emerging materials for gas separation applications. The aim of this article was to synthesize new film-forming polyimides containing imidazolium groups (PI-IMs) and establish their structure-performance relationship. In this context, a new aromatic diamine, namely, N-1-(4-aminophenyl)-N-1-(4-(2-phenyl-1H-imidazol-1-yl)phenyl)benzene-1,4-diamine (ImTPADA), was synthesized and polycondensed with three aromatic dianhydrides, namely, 4,4-(hexafluoroisopropylidene)diphthalic anhydride, 4,4-(4,4-isopropylidenediphenoxy) bis(phthalic anhydride), and 4,4-oxydiphthalic anhydride to form the corresponding polyimides containing pendent 2-phenylimidazole groups (PI-IEs). Next, PI-IMs were prepared by N-quaternization of pendent 2-phenylimidazole groups present in PI-6FDA using methyl iodide followed by anion exchange with bis(trifluoromethane)sulfonimide lithium salt (LiTf2N). PI-IEs and PI-IMs exhibited reasonably high molecular weights, amorphous nature, good solubility, and could be cast into self-standing films from their DMAc solutions. Thermogravimetric analysis showed that 10% weight loss temperature of PI-IEs and PI-IMs were in the range 545-475 degrees C and 303-306 degrees C, respectively. Gas permeability analysis of films of PI-IEs and PI-IMs was investigated by variable-volume method and it was observed that incorporation of ionic groups into PI-6FDA resulted in increased permeability while maintaining selectivity. In particular, polymer bearing Tf2N- anion exhibited high CO2 permeability (33.3 Barr) and high selectivity for CO2/CH4 (41.1) and CO2/N-2 (35.4). (c) 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2018, 56, 1721-1729